2017
DOI: 10.1530/rep-16-0386
|View full text |Cite
|
Sign up to set email alerts
|

Molecular actions of vitamin D in reproductive cell biology

Abstract: Vitamin D (VitD) is an important secosteroid and has attracted attention in several areas of research due to common VitD deficiency in the population, and its potential to regulate molecular pathways related to chronic and inflammatory diseases. VitD metabolites and the VitD receptor (VDR) influence many tissues including those of the reproductive system. VDR expression has been demonstrated in various cell types of the male reproductive tract, including spermatozoa and germ cells, and in female reproductive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 103 publications
(93 reference statements)
1
16
0
Order By: Relevance
“…In contrast to previous reports, 8,27,44 we show here that VDD alone (without hypocalcemia) did not reduce sperm cell motility, regardless of the severity of VDD. We therefore reinforce the idea that the previously reported reduction in sperm motility in VDD cases was likely a calcium‐mediated effect, as suggested 8,27‐49 . The results of our experiments are therefore in complete agreement with Sun et al 27 who demonstrated that VDD is accompanied by decreased extracellular calcium and phosphorus levels and that defective sperm motility in these situations can be overcome by calcium and phosphorus supplements.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to previous reports, 8,27,44 we show here that VDD alone (without hypocalcemia) did not reduce sperm cell motility, regardless of the severity of VDD. We therefore reinforce the idea that the previously reported reduction in sperm motility in VDD cases was likely a calcium‐mediated effect, as suggested 8,27‐49 . The results of our experiments are therefore in complete agreement with Sun et al 27 who demonstrated that VDD is accompanied by decreased extracellular calcium and phosphorus levels and that defective sperm motility in these situations can be overcome by calcium and phosphorus supplements.…”
Section: Discussionsupporting
confidence: 93%
“…However, the conclusions of previous studies have not been completely consistent. For example, it remains unclear whether there is a relationship between VD de ciency status and PCOS in infertile women (11).Comparison of the VD levels between patients with PCOS and in the control group showed no signi cant difference (11 vs. 17 ng/ml, respectively). In recent years, many related studies have shown that the VD content in patients with PCOS may be closely related to metabolic syndrome.…”
Section: Relationship Between the Season Or Age And The Vitamin D Levelmentioning
confidence: 97%
“…The synthesis and activity CYP27B1 is usually regulated by the fibroblast growth factor 23 (FGF-23) [14]. Once activated, the vitamin D binds to different VDRs on different cells where it can activate transcription of different genes, thus exerting a hormone-like effect [2,15,16]. Other than skin, vitamin D can also be acquired through diet.…”
Section: Synthesis Of Vitamin Dmentioning
confidence: 99%
“…Foods rich in vitamins D 3 and D 2 are processed in the digestive tract; then, the liberated vitamin D is transported to the liver via human serum vitamin D-binding protein (DBP). After this point, the process of conversion follows the previous pathway to the liver [15]. Vitamin D is regulated by the enzyme CYP24A1 that catabolizes excess 25(OH)D3, a metabolite of vitamin D, to calcitroic acid, which is excreted through bile [17].…”
Section: Synthesis Of Vitamin Dmentioning
confidence: 99%